Building networks on the fly [cellular radio]. - Pascoe, R.
In this paper, the author describes how, in order to communicate digitally, anywhere, any time, cell phones and other devices need built in connectivity, or discovery, software that works automatically over all sorts of networks
Keywords: Salutation protocol; Cell phones; Cellular radio; Communication networks; Communication software; Connectivity; Digital communication; Discovery protocol